Estudo dos resíduos gerados na eta de anápolis-go: caracterização e quantificação - (:unkn) unknown (Universidade Estadual de Goiás, 2011)
The Water Treatment Plant (WTP), also considered processing industries, generate waste like the sludge from the clarifiers and backwash water from filters, which need proper treatment and disposal in order to avoid any contamination or generation of negative impacts on the environment. The Anápolis Water Treatment Plant has no information on their waste, being necessary a study to form a database to allow future studies of treatment, or use of these wastes to minimize impacts on waste generation by WTP, improving the sustainability of the system. This work aimed to study the physical, chemical and bacteriological and quantification of waste generated at the Anápolis WTP, which has a full cycle and performs a daily discharge of its waste. The characterization and quantification of waste was conducted by means of six samples of sludge from clarifiers and filter backwash water, between the months of August 2010 to January 2011. The sludge samples were obtained in the sludge discharge in a lateral channel next to the decanters, and backwash water was collected on the filter itself during washing, always forming composite samples. The catchment of raw water from Piancó Creek (Ribeirão Piancó) was also analyzed during the same period, to analyze and compare the results of waste analysis. For characterization, the following were analyzed: apparent color, turbidity, pH, alkalinity, conductivity, temperature, chemical oxygen demand, dissolved oxygen, acidity, total solids, suspended solids, total dissolved solids, metals (aluminum, iron and manganese), total coliform and Escherichia coli. Quantification of sludge was performed using the empirical formulas suggested by Kawamura, Cornwell, Richter, AWWA and WRC, and the filter backwash water was quantified by an ultrasonic flow meter in the WTP itself. The waste characterization showed that the sludge cannot be put into a water body without receiving adequate treatment because of its high concentration of metals (aluminum and iron) and large amount of settleable solids, above those permitted by CONAMA Resolution Nº. 357/2005. The WTP flow (890 L.s-1) is above the projected (max. 800 L.s-1), reducing its efficiency, overloading the filters, requiring an increase in the frequency of cleaning them, generating a daily average loss of 1200 m3 of drinking water. The filter backwash water can be reused in the WTP itself, returning to the beginning of the treatment process if it has the characteristics of the water catchment (Class 2). The study showed that some parameters are above acceptable, for example: turbidity (average113 NTU) and the amount of metals present (average 12.5 mg.L-1 aluminum and iron 14.9 mg.L-1), requiring a study to optimize the process, ensuring that these characteristics are within the permitted standard. The analysis of the raw water showed in some parameters such as the solid series, the growth tendency of drought to rain, which can overload the system affecting the efficiency of the process. The rate of sludge settling (RSS) is directly related to the total dissolved solids (TDS) of the filter water washing because the high rate of sedimentation reduces the passage of TDS to the filters.
Keywords: Lodo; Decantadores; Água de lavagem e filtros; Sludge, backwash water and filters; Clarifiers; Backwash water and filters.; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA; ENGENHARIAS::ENGENHARIA SANITARIA